2017
DOI: 10.1007/s11356-017-0865-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of health condition in methyl isocyanate (MIC)-exposed survivors measured after 30 years of disaster

Abstract: Health effects of methyl isocyanate (MIC) exposure were mostly reported on the one-time acute exposure in Bhopal population. Epidemiological survey conducted by the Indian apex body of health research has been reported as Technical Reports, which were lacking in peer review by the expert epidemiologic scientists. The present pilot survey was aimed to measure the health effects 30 years post disaster in MIC-exposed survivors. Questionnaire-based survey has captured every health complaint in 168 individuals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[ 27 ] Thus, the confounders can be lifestyle, living environment, nutritional factors, drinking water, and occupational exposure to other toxicants. [ 28 ] Ipek et al . [ 29 ] had opined that alterations in NDI value are directly related to the proliferative ability of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Thus, the confounders can be lifestyle, living environment, nutritional factors, drinking water, and occupational exposure to other toxicants. [ 28 ] Ipek et al . [ 29 ] had opined that alterations in NDI value are directly related to the proliferative ability of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer incidence in Bhopal has been reported by ICMR (National Cancer Registry Programme 2010). A questionnaire-based survey has reported the spectrum of health status (Ganguly et al 2018b); however, the information could not be corroborated with the medical records since the records are being maintained by the health care providers. Therefore, information on risk of disease-susceptibility could not be established.…”
Section: Discussionmentioning
confidence: 99%
“…Several acute and chronic effects connected to isocyanate exposure have been reported, such as irritation of the eyes, skin, mucous membranes, and respiratory system, asthma, and reduced lung function (Lépine et al 2020 ). A study of the long-term effects of one-time high-dose exposure reported the occurrence of diseases such as diabetes, hypertension, cancer, reproductive outcomes, and respiratory/orthopaedic/general morbidity in the exposed population (Ganguly et al 2018 ).…”
Section: Groups Of Under-researched Cecsmentioning
confidence: 99%